1995
DOI: 10.1002/jlac.1995199508196
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective reformatsky reaction of methyl bromodifluoroacetate

Abstract: The Reformatsky reagent 2 generated from methyl bromodifluoroacetate is added to benzaldehyde in the presence of carbinols 3a, b, amino alcohols 3c-g, or amino alkoxide 3h. N-Methylephedrine 3c provides the highest enantioselectivity in the formation of the adduct S-4a (84 YO ee; >96 % after recrystallization) whose absolute configuration is determined by an X-ray structural analysis of the amide 6.Many fluorinated organic compounds display substantial and unexpected biological activity. Since the fluorine ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…Braun et al and Andrés et αϊ. have independently reported that the Reformatsky reagents generated from bromodifluoroacetates react with aromatic aldehydes in the presence of stoichiometric amounts of chirai amino alcohols such as iV-methylephedrine to afford the corresponding desired aldols in good optical yields (22,23). However, these methods are not catalytic, and the decrease in quantity of the chirai ligands dramatically suppresses the enantioselectivity.…”
Section: Catalytic Asymmetric Aldol Reaction Of Fluorine-substituted mentioning
confidence: 96%
“…Braun et al and Andrés et αϊ. have independently reported that the Reformatsky reagents generated from bromodifluoroacetates react with aromatic aldehydes in the presence of stoichiometric amounts of chirai amino alcohols such as iV-methylephedrine to afford the corresponding desired aldols in good optical yields (22,23). However, these methods are not catalytic, and the decrease in quantity of the chirai ligands dramatically suppresses the enantioselectivity.…”
Section: Catalytic Asymmetric Aldol Reaction Of Fluorine-substituted mentioning
confidence: 96%
“…In the presence of stoichiometric amounts of chiral amino alcohols, such as methylephedrine, this reaction affords the corresponding products with moderate enantioselectivity [27].…”
Section: Synthesis By C-c Bond Formation Of Partially Fluorinated Buimentioning
confidence: 99%
“…Two recent examples use ephedrine derivatives; in one case for the addition of a lithium acetylide to a trifluoromethyl aryl ketone in 96-98% ee, 84 and in the second for an enantioselective Reformatsky reaction (Scheme 24). 85 Two equivalents of N-methylephedrine 57 are required to give the product in 84% ee, with three equivalents of organozinc reagent, since deprotonation of 57 occurs. Sub-stoichiometric amounts of 57 give reduced selectivities (54% ee with 0.1 equiv.…”
Section: Miscellaneous Uses Of Chiral Reagentsmentioning
confidence: 99%